Reinterpretation of Etymology in Pop Culture: The Transformation of Language and Identity Through Film and Music - Muliawan, Pondra; Nugraha, Rahmat Mulya; Mulyani, Noni (CV. Goresan Pena, 2025)
This study explores the phenomenon of semantic change in language influenced by pop culture, particularly through film and music. The use of terms in these media, which carry social and cultural implications, triggers shift in communication styles and the formation of social identity. The aim of this research is to examine how the etymology of words popularized by film and music undergoes semantic transformation and how this process affects broader social values. A qualitative method with a literature review approach was employed, analyzing data from various films, songs, and scholarly sources. The findings indicate that terms emerging in film and music often become symbols of social change, introducing new concepts that enrich everyday language. This transformation not only reflects societal shifts but also fosters global cultural connectivity.